QSAR STUDY OF 1,10-PHENANTHROLINE DERIVATIVES AS THE ANTIMALARIAL COMPOUNDS USING ELECTRONIC DESCRIPTORS BASED ON SEMIEMPIRICAL AM1 CALCULATION - Mustofa Mustofa; Iqmal Tahir; Jumina Jumina (Indonesian Journal of Chemistry, 2002)
Quantitative Structure-Activity Relationship (QSAR) analysis of 1,10-phenantroline analogs as antimalarial drug has been conducted using atomic net charges (q) as predictors of their activity. Data of predictors are obtained from computational chemistry method using semi-empirical molecular orbital AM1 calculation. Antimalarial activities are taken as the activity of the drugs against plasmodium falciparum (FcM29-Cameroun) strain and are presented as the value of ln(1/IC50) where IC50 is an effective concentration inhibiting 50 % of the parasite growth.  The results show that there is correlation between antiplasmodial activity and electronic structure as represented by a linear function of activity versus atomic net charges of N1, C7, C10, C14 atoms on the 1,10-phenanthroline skeleton and is expressed by :log IC50 = -3,4398 - 14,9050 qN1 - 8,5589 qC10 - 14,7565 qC7 + 5,0457 qC11The equation is significant at 95% level with statistical parameters : n = 13; r = 0,96275; r2 = 0,92689; SE = 0,61578 and F (4,8) = 25,3556.